New economy: Explosive growth driven by a productivity revolution? - Christoph Scherrer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The discussion paper discusses the macroeconomic argument of a New Economy that is characterized by higher non-inflationary economic growth due to increases in productivity caused by the digital revolution. Besides presenting evidence put forward by mainstream protagonists of the New Economy, it explores an interpretation of the New Economy inspired by regulation theory. Specifically, it looks at the stability of a financeled regime of accumulation on the basis of the digital production paradigm. Some basic causal relationships of such a regime, especially the investment-profits, wealth-profits, and wealth-consumption connections, seem too fragile to be able to support the assertion that a stable new regime of accumulation has emerged. Furthermore, the New Economy thesis suffers from serious problems in measuring productivity in the service industries. Therefore, it seems just as plausible that the long “Clinton” expansion was a singular event made possible by the special position the U.S. enjoys in the world economy. – – Wie stimmig ist das makroökonomische Argument von einer New Economy: Ist höheres inflationsneutrales Wirtschaftswachstum aufgrund gestiegener, der digitalen Revolution geschuldeten Produktivitätszuwächse möglich geworden? Zur Beantwortung dieser Frage werden zunächst die von den Mainstream Befürwortern angeführten Belege präsentiert. So dann wird eine Interpretation aus regulationstheoretischer Perspektive versucht, wobei insbesondere die Stabilität eines finanzgetriebenes Wachstumsmodells auf der Basis eines digitalen Produktionsregimes ausgelotet wird. Einige fundamentale Kausalzusammenhänge eines solchen Modells, wie der Investitionen-Gewinn-Nexus, Vermögen- Gewinn-Nexus und Vermögen-Konsum-Nexus, sind zu fragil, um von einem neuen stabilen Akkumulationsregime sprechen zu können. Ferner steht der Kern der New- Economy-These, die informationstechnologisch bedingten Produktivitätszuwächse, noch auf unsicherem Datenfundament. Deshalb erscheint eine Interpretation des langanhaltenden Wirtschaftsaufschwunges in den USA als singuläres, durch die besondere Position der USA in der Weltwirtschaft begünstigtes Ereignis ebenso plausibel zu sein.
Keywords: 300; Internet; Kapitalismus; Wirtschaftliche Instabilität; Theorie; USA; New Economy